the Penyuluhan Bahaya Efek Radiasi Pada Ibu Hamil Di Posyandu Merangkai Bunga Setaman, Puskesmas Karya Wanita Kota Pekanbaru - Hulmansyah, Danil; Bisra, Marido; Yoshandi, T. Mohd.; Angella, Shelly (Komunitas Manajemen Kompetitif, 2024)
Abstract: The use of X-ray radiation is currently widely used in the medical world as a diagnostic tool or therapy for diseases. X-ray radiation in the field of health, especially medicine, is used as radiography which plays a role in diagnosing a disease by depicting the anatomical structure of the human body. Pregnant women are women who have a fetus developing in their womb. Pregnant women are advised to pay attention to adequate nutritional intake. Conduct regular pregnancy check-ups, avoid smoking and alcoholic beverages and maintain personal and environmental hygiene. The purpose of this community service is to provide knowledge about radiation to pregnant women and the community in general. The method used is counseling and providing understanding to pregnant women so that they understand more deeply about the dangers of radiation. The benchmark for this understanding is carried out by using the distribution of pre-post test questionnaires to conduct counseling.